Nootropics in Complex Therapy of Chronic Cerebral Ischemia - Chekman, I.S.; Belenichev, I.F.; Demchenko, A.V.; Bobrova, V.I.; Kucherenko, L.I.; Gorchakova, N.A.; Bukhtiyarova, N.V. (Science and Innovation, 2024)
The clinical and pharmacological characteristics of nootropics as one of the most effective groups of neuropsychotropic drugs have been considered. The nootropics has been classified by the principal mechanism of action. The examples of clinical use of drugs on patients with chronic cerebral ischemia have been given.